Machine Learning-Enhanced Root Cause Analysis for Rapid Incident Management in High-Complexity Systems - Subba Rao Katragadda; Brij Kishore Pandey; Sudhakar Reddy Peddinti; Ajay Tanikonda (Journal of Science & Technology, 2022)
Root cause analysis (RCA) is an essential process in managing incidents and ensuring the reliability and stability of high-complexity systems, particularly in domains such as information technology, manufacturing, and critical infrastructure. However, traditional RCA approaches often fall short in addressing the growing intricacy of modern systems, characterized by large-scale, interconnected components and multidimensional datasets. This study explores the integration of machine learning (ML) techniques into RCA to accelerate incident resolution, enhance accuracy, and bolster operational efficiency. By leveraging advanced ML algorithms, such as supervised learning for anomaly detection, unsupervised clustering for data pattern identification, and reinforcement learning for adaptive decision-making, machine learning-enhanced RCA presents a transformative approach to incident management. Machine learning offers significant advantages by automating the identification of causal relationships in high-dimensional datasets, thereby reducing the reliance on manual expertise and domain-specific heuristics. Through feature extraction and dimensionality reduction techniques, ML models can process vast amounts of structured and unstructured data, including log files, sensor readings, and network traces, to identify root causes more effectively. This capability is especially critical in high-complexity systems where latent relationships between system components often contribute to cascading failures. The study discusses the application of ensemble methods, such as random forests and gradient boosting, to improve the robustness of root cause detection, as well as the use of neural networks and deep learning techniques for uncovering non-linear dependencies within datasets. To contextualize the practical implications of machine learning-enhanced RCA, this paper presents case studies from industries that operate high-complexity systems. Examples include IT incident management in cloud computing environments, predictive maintenance in manufacturing systems, and fault detection in power grids. These case studies demonstrate how ML-driven RCA can reduce incident resolution times, minimize operational downtime, and enhance decision-making by providing actionable insights in real time. Furthermore, the integration of natural language processing (NLP) for automated log analysis and graph-based ML models for system dependency mapping are explored as advanced techniques for enhancing RCA capabilities. Despite its advantages, the implementation of ML-enhanced RCA is not without challenges. This paper addresses key obstacles, such as data quality issues, the need for interpretability in ML models, and the potential for overfitting in complex environments. The ethical implications of automated decision-making in RCA and the role of human oversight in validating ML-driven insights are also discussed. The study emphasizes the importance of designing hybrid approaches that combine machine learning with domain expertise to ensure accurate and contextually relevant outcomes. Moreover, this paper investigates the scalability of ML-enhanced RCA systems, particularly in dynamic and distributed environments. The role of edge computing in processing real-time data and the adoption of federated learning for cross-organization collaboration are highlighted as critical enablers for scaling ML-based RCA solutions. Security considerations, including the risk of adversarial attacks on ML models and the need for robust data governance frameworks, are analyzed to ensure the reliability and trustworthiness of ML-enhanced RCA systems. The future of RCA in high-complexity systems lies in the development of autonomous and self-healing systems. This study discusses the potential of integrating ML-enhanced RCA with emerging technologies, such as digital twins and blockchain, to enable proactive incident management and predictive failure analysis. By combining ML capabilities with advanced system modeling and immutable data storage, organizations can achieve a higher degree of resilience and reliability in their operations. Additionally, this paper explores the role of explainable AI (XAI) in bridging the gap between ML-driven RCA insights and human decision-makers, ensuring transparency and trust in automated incident management processes.